Crossing Malmquist systems with certain types - Wang, F. N.; Liu, K. (Հայաստանի ԳԱԱ)
In this paper, we will present the expression of meromorphic solutions on the crossing differential or difference Malmquist systems of certain types using Nevanlinna theory․
Keywords: Mathematics